Dampak Berjudi dalam Pandangan Islam - Muhammad Reyhan Givani Hendrasjah; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the negative impact of gambling behavior in the Islamic view. The method used in this research is qualitative through literature study. The results and discussion of this study are that in Islam gambling is described as